2016
DOI: 10.1155/2016/1203285
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage, Oxidative Stress, and Antioxidant Therapy

Abstract: Hemorrhagic stroke is a common and severe neurological disorder and is associated with high rates of mortality and morbidity, especially for intracerebral hemorrhage (ICH). Increasing evidence demonstrates that oxidative stress responses participate in the pathophysiological processes of secondary brain injury (SBI) following ICH. The mechanisms involved in interoperable systems include endoplasmic reticulum (ER) stress, neuronal apoptosis and necrosis, inflammation, and autophagy. In this review, we summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(188 citation statements)
references
References 197 publications
(206 reference statements)
4
177
0
1
Order By: Relevance
“…Accumulating evidence has demonstrated that oxidative stress plays an important role in the development of EBI (Ayer and Zhang, 2008; Duan et al, 2016). Following insults like hypoxia-ischemic or SAH, the production of reactive oxygen species (ROS) exceeds the ability of the endogenous anti-oxidant system, leading to oxidative stress and cell death (Wu et al, 2014; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that oxidative stress plays an important role in the development of EBI (Ayer and Zhang, 2008; Duan et al, 2016). Following insults like hypoxia-ischemic or SAH, the production of reactive oxygen species (ROS) exceeds the ability of the endogenous anti-oxidant system, leading to oxidative stress and cell death (Wu et al, 2014; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reaction and cell apoptosis importance has increased in the ICH process, which leads to cerebral edema and secondary brain injury 21,22. Activation of neutrophils, macrophages and microglia enhances secretion large amount of inflammatory factors, such as TNF-α, IL-1β, IL-6 and IL-8, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, CBS activation named S-adenylyl methionine was revealed which efficiently decreased in individuals with AD [31] because when endogenous level of H 2 S decreases, it causes accretion of homocysteine level in the brain eventually [151]. Many studies including in vitro and in vivo studies shows that H 2 S has a prominent role in cell growth promotion and preservation of the function of the factors like amyloid beta (A β ) peptides, malondialdehyde (MDA), hypochlorite (HOCL), and 4-hydroxy-2-nonenal (4-HNE) which causes oxidative stress [15, 152]. In a study of adult male Wister rats, null H 2 S toxicity has the capacity to increase cognition by lowering A β plaques and triggering the APP, PST, and ON/4R-tau isoforms.…”
Section: Oxidative Stress and Gasotransmittersmentioning
confidence: 99%